1988
DOI: 10.1159/000185143
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Trial of Thymopentin in Hemodialysis Patients Who Fail to Respond to Hepatitis B Vaccination

Abstract: Uremic patients are at high risk of hepatitis B virus (HBV) infection and, despite the availability and efficacy of hepatitis B vaccine, a high rate of non responders has been reported. Forty uremic patients undergoing maintenance hemodialysis who failed to produce any measurable anti-HBs antibody response after 4 administrations of 5 μg of Hevac B Pasteur vaccine were admitted to a randomized controlled clinical trial. Group A (14 patients) received 3 doses of 5 μg s.c. each of vaccine at monthly intervals an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 13 publications
0
21
1
1
Order By: Relevance
“…The yeast-derived vaccine is not more immunogenic than the plasma-derived vaccine and nonresponse to one type is generally not overcome by vaccination with the other. Some authors reported an increase in anti-HBs response with co-administration of zinc [136,137], erithropoietin [100], or immunomodulators such as alfa- [138] or gamma- [139] interferon, thymopentine [140][141][142], interleukin-2 [143][144][145], and granulocytemacrophage colony-stimulator factor [146]. In addition, some investigators proposed to vaccinate uremic patients before they become dialysis-dependent [147,148].…”
Section: Hbv Vaccination In Dialysis: Short-term Studiesmentioning
confidence: 99%
“…The yeast-derived vaccine is not more immunogenic than the plasma-derived vaccine and nonresponse to one type is generally not overcome by vaccination with the other. Some authors reported an increase in anti-HBs response with co-administration of zinc [136,137], erithropoietin [100], or immunomodulators such as alfa- [138] or gamma- [139] interferon, thymopentine [140][141][142], interleukin-2 [143][144][145], and granulocytemacrophage colony-stimulator factor [146]. In addition, some investigators proposed to vaccinate uremic patients before they become dialysis-dependent [147,148].…”
Section: Hbv Vaccination In Dialysis: Short-term Studiesmentioning
confidence: 99%
“…As in trials with pooled plasma vaccines, also with the safer recombinant antigen a consistent fraction of nonresponders (NR; 35-60%) should be forecast [1][2][3]. In order to increase the chances of response and to shorten its time, a number of schedules of vaccine administration and expensive immunotherapies have been suggested, prolonging trials for NR, with relative success [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…As in trials with pooled plasma vaccines, also with the safer recombinant antigen a consistent fraction of nonresponders (NR; 35-60%) should be forecast [1][2][3]. In order to increase the chances of response and to shorten its time, a number of schedules of vaccine administration and expensive immunotherapies have been suggested, prolonging trials for NR, with relative success [2,3]. Some good results have been recently obtained with mul tiple low-dose intradermal injection, with the drawbacks of local pain, staff engagement and short-life antibody titers [4], As NR show resistence to further immunization, we postulated that thay could be regarded as a separate set of patients and probably preselected by immune parameters.…”
Section: Introductionmentioning
confidence: 99%
“…KBH hastalarında hepatit B aşılamasına yeterli cevap alınabilmesi için yüksek doz ve daha sık enjeksiyon yapılması önerilmiştir [10,18]. İmmün cevabı artırmak için çift doz aşılama yapılması, düşük antikor titresi elde edilirse booster doz yapılması [19][20][21][22][23], enjeksiyon şeklinin değiştirilmesi (intradermal veya intramüsküler), immün sistemi indükleyen ajanların eklenmesi [24][25][26][27] ve hepatit A ve B aşısının kombine verilmesi [28] gibi çeşitli yöntemler uygulanmıştır. [7] tarafından yapılan bir metaanalizde diyaliz türünün aşı yanıtı üzerine etkisinin olmadığı, genç hastalarda aşı yanıtının daha yüksek olduğu bildirilmiştir.…”
Section: Discussionunclassified